Artysta w l'univers concentrationnaire. "Kornblumenblau" Leszka Wosiewicza jako traktat o sztuce - Mąka-Malatyńska, Katarzyna (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2010)
The author of the essay considers Leszek Wosiewicz’s Kornblumenblau as a film about art and focuses on the self reflexive elements present in the film, particularly those referring to film conventions. This analysis examines the film in the context of the reflections about the meaning of art in totalitarian systems and situation of the artist in the reality of the concentration camp. Kornblumenblau depicts degenerated art as depriving of freedom and rescue, becoming another tool of oppression. Dehumanizing power of this art points at the final decay of man in the epoch of gas chambers.
Keywords: Concentration camp; Dehumanization; Self reflexive; Film conventions; Holocaust; Second world war; tTotalitarian system; Wosiewicz Leszek